Mission-oriented innovation policy in Japan Challenges, opportunities and future options - Larrue, Philippe (OECD Science, Technology and Industry Policy Papers, 2021)
This report assesses the potential for mission-oriented innovation policies (MOIPs) to contribute to the sustainable transition in Japan, and examines the challenges and opportunities that MOIPs would present. As part of a series of MOIP national case studies, the report finds that the ongoing ambitious and top-down MOIPs led by the center-of-government build upon a long history of proactive and goal-oriented policy intervention. MOIPs in Japan are the latest step of decades of efforts to reduce the fragmentation and lack of holistic coordination of Japan's science, technology and innovation policy in order to proactively address societal challenges. Available evaluations of these policies demonstrate very encouraging results in that regards. The study concludes with recommendations to pursue these efforts, including by mainstreaming these policy initiatives across the government structure and complementing them with more bottom-up challenge-based initiatives